JOB SATISFACTION AMONG PHYSICAL EDUCATION TEACHERS FROM THE MUNICIPAL NETWORK OF SÃO JOSÉ-SC - Raquel Krapp do Nascimento; Alexandra Folle; Alzira Isabel da Rosa; Jorge Both (Journal of Physical Education)
ABSTRACT The aim of this study was to analyze job satisfaction among physical education teachers. Seventy-three physical education teachers from the municipal network of São José (SC) participated in this study. For data collection, two instruments were used: socio-demographic questionnaire and the "Scale for Assessment of Quality of Life at Work Perceived by Physical Education Teachers". The following tests were used in statistical analysis: chi-square for single group and Mann-Whitney U-test. Results showed that teachers were satisfied in the overall assessment and in dimensions referring to career development, autonomy, laws. regulations and job's social relevance, being dissatisfied with their remuneration. Results also revealed that teachers with more than four years working in the municipal network were more satisfied in the overall assessment and in the social relevance dimension, while teachers with 10 or more years of teaching practice were satisfied with career development, social relevance, autonomy and social integration dimensions.